2006
DOI: 10.1007/s10533-006-9043-5
|View full text |Cite
|
Sign up to set email alerts
|

Relating land cover to stream properties in southern Chilean watersheds: trade-off between geographic scale, sample size, and explicative power

Abstract: Several studies relating land cover to stream properties have used sample sizes of more than 100 watersheds, but the variance that they explain is moderate to low (R 2 less than 50%), limiting the predictive value of these studies when their models are applied to watersheds that were not included in the models' development. We hypothesize that this is due to the increases in variation that occur with increases in sample size and in the geographic scales of the areas in which the watersheds are distributed. Lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…In our study, the differences in DIN retention were evident between native forests and Eucalyptus plantation, as also has been described previously by [12]. However, [35] observed using land cover, watershed area and precipitation as predictors for water quality (nitrate, ammonia, DON, TDP and electric conductivity) for local models explained 79.5% of the variance. …”
Section: Throughfall Enrichment Factorssupporting
confidence: 89%
“…In our study, the differences in DIN retention were evident between native forests and Eucalyptus plantation, as also has been described previously by [12]. However, [35] observed using land cover, watershed area and precipitation as predictors for water quality (nitrate, ammonia, DON, TDP and electric conductivity) for local models explained 79.5% of the variance. …”
Section: Throughfall Enrichment Factorssupporting
confidence: 89%
“…Numerous studies have shown that variations in nutrient and sediment concentration and export in stream water are a function of changes in forest land cover, watershed properties, and precipitation (e.g. Graham, ; Strayer et al ., ; Cuevas et al ., ; Little et al ., ). The importance of forest stream buffers to conserve stream water quality has been recognized in North America and Europe for several decades, but much of the work on dissolved N and forest buffers has been performed in N‐saturated systems (Osborne and Kovacic, ).…”
Section: Discussionmentioning
confidence: 98%
“…These changes may affect the abundance of aerobic and anaerobic microorganisms and subsequently affect the cycling of several elements, including N (Huygens & Boeckx, ). However, Cuevas et al () observed that land cover and watershed area explained nearly 90% of the variability in water quality (NO 3 − − N, NH 4 + − N, DON, Total‐P, and electric conductivity) using local models on dry season. However, during wet season, land cover and watershed area just explained 70%, and with the addition of geomorphology and precipitation, it explained 85%.…”
Section: Discussionmentioning
confidence: 99%
“…Water quality control is recognized as one of the main ecosystem services provided by forests (Alexander, Boyer, Smith, Schwarz, & Moore, ). Several authors have found that different land cover (Cuevas et al, ; Oyarzún, Aracena, Rutherford, Godoy, & De Schrijver, ; Vitousek et al ., ), forest type (De Schrijver et al, ), and hydrology (Campbell et al . , ) affect N and P cycling in forests and have a direct impact on nutrient exports to streams.…”
Section: Introductionmentioning
confidence: 99%